Point-of-care tests, diagnostic uncertainty and antimicrobial stewardship in the ICU: procalcitonin or PCR to aid antibiotic-stop decisions – an observational cohort study - Luke Moore; Suveer Singh; Martine Nurek; Nabeela Mughal; Timothy Lau; Archit Singhal (BMJ Open)
Objectives Intensive care unit (ICU) clinicians stop antibiotics more often, with a negative infection: point-of-care test (PCR-POCT). Simulated cases of diagnostic uncertainty regarding infection resolution led clinicians to choose options such as procalcitonin (PCT) and/or PCR-POCTs +/− de-escalation to aid stop decisions. We hypothesised that a direct infection indicator, PCR-POCT, would influence stop judgements more than indirect PCT. Accordingly, we tested antibiotic-stop decisions when presented with a negative PCR-POCT despite borderline-positive PCT.Designs Observational prospective study.Setting ICU.Participants 66 ICU clinicians from University hospitals.Methods Clinicians saw four scenarios of different clinico-biological trajectories: (1) clear improvement, (2) clear worsening, (3) discordant—clinically better/biologically worse and (4) discordant—clinically worse/biologically better. Participants gave an initial decision (stop/continue/continue–escalate/continue–de-escalate). Then PCR-POCT and/or PCT was offered (accept/decline). After a negative PCR-POCT and borderline-positive PCT result, a final antibiotic decision was taken.Measures Proportion of stop decisions before versus after test results per scenario. The association of the final decision with the clinician’s change in confidence, willingness to request the biomarker(s) and the case trajectory was determined.Results Fewer clinicians than expected stopped antibiotics versus baseline (36%, 94/264 vs 42%, 110/264, p=0.045). This was so in three of four scenarios, significantly less in the improvement (p<0.001) and the discordant clinically better scenario (p=0.024). PCT was requested more frequently than PCR-POCT (61% vs 53%, p<0.001). PCT requesters (vs declining) were significantly less inclined to stop antibiotics (p<0.001), while PCR-POCT requesting led to more stopping (p<0.001), before knowing the test results.Conclusions A negative PCR-POCT result did not increase clinicians’ inclination to stop antibiotics when alongside a borderline-positive PCT. This reflects clinicians’ natural risk aversion. PCT was more popular than PCR-POCT, but PCR-POCT was more likely to aid stop decisions.Their comparison, role, utility and selective deployment for influencing antibiotic-stop decisions more effectively require a large randomised controlled trial.